Gender Budgeting - Stotsky, Janet (IMF Working Papers; Working Paper, 2006)
Women are disadvantaged relative to men, according to key economic, social, and political measures of equality, but in many areas, such as education, differences are narrowing. The concept of externalities underlies the arguments for including gender considerations in budget programs and policies. Other arguments have a weaker economic basis but may be more socially or politically compelling. The experience to date with "gender budgeting," which entails looking at gender issues comprehensively within the budget, has been mixed. To become more useful, gender budgeting should be integrated into budget processes in a way that generates tangible improvements in policy outcomes. The International Monetary Fund should encourage fiscal authorities to take into account the external benefits of reducing gender inequalities and to remove from fiscal legislation any arbitrary discrimination against women.